Postmenopausal obesity: 12,500 steps per day as a remedy? Relationships between body composition and daily steps in postmenopausal women - Kroemeke, Aleksandra; Zając-Gawlak, Izabela; Pośpiech, Dariusz; Gába, Aleš; Přidalová, Miroslava; Pelclová, Jana (Menopause Review/Przegląd Menopauzalny, 2014)
Introduction: To verify relationships between physical activity (steps per day) and obesity (components of body composition) among postmenopausal women. Material and methods: Physical activity (ActiGraph GT1M accelerometer; worn for 7 days) and obesity (body composition analyzer InBody 720) were assessed among 79 healthy postmenopausal women (age 63.25 ± 5.51 years; range: 51-81 years). In order to determine differences in body composition in women with different levels of physical activity, one-way analysis of covariance (ANCOVA) was conducted, with age of participants as a covariate. Results : Significant intergroup differences in almost all analyzed components of the body composition (weight, body mass index, waist-hip ratio, visceral fat area, body fat mass and percent of body fat) were obtained. Highly active women (≥ 12,500 steps/day) had lower weight and adiposity parameters than those that represented low (< 7,500 steps/day) or somewhat active (7,500-9,999 steps/day) groups. Besides, a noteworthy difference between active (10,000-12,499 steps/day) and low active women was recorded. Noticeably, only in the most active group was the BMI within normal ranges. Conclusions : The higher physical activity, the lower obesity in postmenopausal women. The recommended 10,000 steps/day seems insufficient for this age group. Based on the obtained results, postmenopausal women should walk at least 12,500 steps per day to improve their health.